The Role and Legal Strength of Mediation in Providing Legal Certainty for Song Creators - Ainun Nabilah; Andriyanto Adhi Nugroho; Atik Winanti (Catalist Indo Publisher, 2026)
This study aims to analyze the legal status and effectiveness of mediation in ensuring legal certainty for songwriters in copyright dispute resolution within Indonesia's digital music industry. The research employs a normative juridical method with statutory and conceptual approaches, focusing on relevant regulations and legal doctrines. The findings indicate that mediation is legally recognized as an alternative dispute resolution mechanism and possesses binding force based on the principle of pacta sunt servanda. However, its effectiveness in ensuring legal certainty is conditional. Mediation agreements formalized as court-approved settlement deeds (peace acts) provide stronger legal certainty due to their executorial force, whereas informal agreements lack enforceability. From the perspective of Gustav Radbruch's theory of legal certainty, mediation fulfills the normative aspect but remains limited in terms of predictability and enforceability. Furthermore, the study reveals that disparities in bargaining power between songwriters and industry actors often result in less equitable agreements, raising concerns from the standpoint of proportionality. Despite its advantages in efficiency, flexibility, and relationship preservation, mediation has not fully guaranteed substantive justice and legal protection. Therefore, strengthening the legal framework and institutional implementation of mediation is necessary to ensure balanced, reliable, and effective protection of songwriters' economic and moral rights in copyright disputes.